Emotional Profiles of Novice Teachers without Training at the Beginning of Professional Teaching - Vargas Castro, Erick Zorobabel (2024)
The beginning of teaching involves the confluence of multiple concerns and emotions with novice teachers as protagonists. In this regard, this article describes the emotional profiles resulting from the first teaching experience in upper secondary education in Mazatlán, Sinaloa, México, of professionals with initial training in different areas of knowledge, suddenly being immersed in complex classroom interactions. The research was qualitative, descriptive in scope. The fieldwork derived from the Biographical-Narrative method and two techniques, one main, semi-structured interview, and the other complementary with the narrative in written mode, for thirty teachers, organized into three groups: 1) physical, mathematical and engineering sciences, 2) social sciences, and 3) health sciences. The results showed a trend of concerns related to content mastery, discipline in the classroom, and the individual needs of students as the main causes of emotions ranging from satisfactory and challenging to learning, nervousness, tiredness, or even the desire to quit. It is concluded that there is a significant difference between groups according to a perception of the conflictive school reality and the priority towards different areas of education, whose linking root acquires meaning in relation to accredited initial training.